2022
DOI: 10.3389/fimmu.2022.776861
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Platelet-Endothelium Interactions in the Pathogenesis of Severe SARS-CoV-2 Infection-Associated Myocardial Injury

Abstract: Cardiovascular dysfunction and disease are common and frequently fatal complications of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Indeed, from early on during the SARS-CoV-2 virus pandemic it was recognized that cardiac complications may occur, even in patients with no underlying cardiac disorders, as part of the acute infection, and that these were associated with more severe disease and increased morbidity and mortality. The most common cardiac complication is acute cardiac inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 112 publications
0
25
0
Order By: Relevance
“…These findings can explain the coexistence of vascular and infectious/inflammatory signs in the reported neuroimaging studies of the patients. The pathological documentation of intramural inflammation in the small vessels of the brain is strictly related to the elevated levels of the SARS-CoV-2 receptor ACE2 in the brain vasculature, and it is associated with sign of severe infection and systemic thrombotic and inflammatory involvement [ 36 , 37 , 38 ]. In another autoptic series of ten patients [ 39 ], all brains had neutrophilic microvascular endothelitis, suggesting that vasculitis with autoimmune features occurred in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings can explain the coexistence of vascular and infectious/inflammatory signs in the reported neuroimaging studies of the patients. The pathological documentation of intramural inflammation in the small vessels of the brain is strictly related to the elevated levels of the SARS-CoV-2 receptor ACE2 in the brain vasculature, and it is associated with sign of severe infection and systemic thrombotic and inflammatory involvement [ 36 , 37 , 38 ]. In another autoptic series of ten patients [ 39 ], all brains had neutrophilic microvascular endothelitis, suggesting that vasculitis with autoimmune features occurred in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although severe inflammation is one of the known mechanisms of endothelial activation [35] , Johnson et al have recently found no evidence of cytokine-mediated activation, nor the expression of adhesion proteins such as intercellular adhesion molecule-1 (ICAM-1) and vascular adhesion molecule-1 (VCAM-1) in heart tissue [38] . Furthermore, in an in vitro study, exposure of ECs culture from the coronary artery to the viral nucleocapsid protein stimulates the expression of ICAM-1 and VCAM-1 [39] . Therefore, further investigation is required to clarify this aspect.…”
Section: Molecular Mechanisms Of Sars-cov-2-induced Cardiac Microvasc...mentioning
confidence: 99%
“…NP of SARS-CoV-2 -but not that of other coronaviruses, that is, SARS-CoV, MERS-CoV, HUB1-CoV, and/or H1N1 -can strongly activate human endothelial cells via the engagement of TLR2/NFKB and MAPK signaling pathways. SARS-CoV-2 NP potentiates the expression of ICAM1 and VCAM1, thus promoting monocyte adhesion to endothelial surfaces, as well as such proinflammatory cytokines as SELE, MCP-1/CCL2, IL1B (mRNA), and TNF -a potent inducer of endothelial activation; it is notable that the nature and the magnitude of SARS-CoV-2 NP's effects on the endothelium are comparable to those of TNF (25,26). TNF and various selectins (of endothelial as well as platelet origin) are known to be potent stimulators of von Willebrand factor (vWF) and coagulation factor F8/(F)VIII secretion from the endothelium; in COVID-19, a strong elevation of vWF and F8 secretion from the endothelium has been reported (26,27).…”
Section: Vascular Endotheliummentioning
confidence: 99%